DRUG UTILIZATION REVIEW OF FLUOROQUINOLONES AMONG THE OUT-PATIENTS IN A PUBLIC SECTOR HOSPITAL, PAKISTAN - Awais Arshaad; Shahzaib Sharafat; Ayesha Mustafa; Hamza Mahmood; Fatima Mustafa; Sonia Tariq; Ammara Asif (International Journal of Pharmacy & Integrated Health Sciences)
Background: The increase in antibiotic resistance is a challenging threat to the healthcare system. Irrational drug use, polypharmacy and the current epidemic of bacterial resistance is attributed to the over use of anti-microbial drugs. Objectives: The aim of the current study is to evaluate the utilization pattern of fluoroquinolones, to find significant difference between defined daily dose and prescribed daily dose of such antibiotics. Methodology: Quantitative observational, retrospective study was performed to measure the use of antibiotics, specifically Fluoroquinolones in the northern region of Punjab, Gujranwala District, Pakistan. Total 300 patients were enrolled in this study. Data was collected from the patients of all age regardless of their gender, by prescription review. Results: Total 300 prescriptions were reviewed to evaluate the prescription pattern of fluoroquinolones in outpatients. Out of 300 prescriptions, the average number of drugs per prescription was 4.5, maximum number of drugs per prescription was 8 and minimum one drug was prescribed in 28 (9.3) prescriptions. The number of prescriptions that contains the drugs without generic names were 71 (23.7) and which contains one drug with generic names were 203 (67.7). Encounter with antibiotic and injection prescribed were 79.3% and 5.3%, respectively. The most commonly prescribed anti-biotic was ciprofloxacin followed by levofloxacin (maximum defined daily dose). Conclusion: In this study we observed the drug utilization review of fluoroquinolones antibiotics by evaluating the prescribing patterns among the outpatients. All the study drugs were prescribed by their brand names rather than generic names which is not a rational prescribing and utilization pattern, leading to the enforcement of antibiotic stewardship program.